'No space of our own': The vanishing South Indian hunter-gatherers' experience in space sharing. Issue 3 (April 2019) - Kakkoth, Seetha
Abstract : This paper examines rapid development during the last six decades (1962–2016) of sharing in various realms (residential, socio-cultural, economic, political and religious) between Aranadan – a vanishing hunter-gatherer tribe in Nilambur valley, South India – and their neighbours. The Aranadan tribe in Nilambur Valley of Malappuram district, Kerala, had a population below 300 in 2015. Until they were resettled in government colonies in the 1970s they were leading a semi-nomadic life in the lower valley of Nilambur forests and had little contact with non-tribal people. These colonies located in the fringes of forests are surrounded by non-tribal people. It has been observed that during the course of time the interaction of the Aranadan with their non-Aranadan neighbours has increased significantly, slowly paving the way for the non-Aranadan to share their dwelling space. They have unhesitatingly shared their physical and metaphysical space with neighbouring dominant cultures, even while realising that there remains little space of their own.